2020
DOI: 10.3389/fphys.2020.01113
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cardiac Macrophage and Cytokines on Ventricular Arrhythmias

Abstract: In the heart, cardiac macrophages have widespread biological functions, including roles in antigen presentation, phagocytosis, and immunoregulation, through the formation of diverse cytokines and growth factors; thus, these cells play an active role in tissue repair after heart injury. Recent clinical studies have indicated that macrophages or elevated inflammatory cytokines secreted by macrophages are closely related to ventricular arrhythmias (VAs). This review describes the role of macrophages and macrophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 119 publications
(144 reference statements)
0
12
0
6
Order By: Relevance
“…In addition, the positive effect exerted by hypoxia exposure on cardiomyocyte proliferation (discussed in the "Oxygen levels" section), has been suggested to be dependent on an increase in the number of resident macrophages (56). In contrast to the neonatal stage, adult mammalian hearts mainly undergo repair processes based on scarring and fibrosis, mostly as a result of the interaction between infiltrating immune cells (including macrophages) and fibroblasts [reviewed by Chen and colleagues (74)]. The paradoxical role of macrophages, triggering cardiac regeneration in lower vertebrates and neonatal mammals, and maladaptive remodeling in injured adult mammals, has been a matter of investigation.…”
Section: Cardiac Cell Populationsmentioning
confidence: 99%
“…In addition, the positive effect exerted by hypoxia exposure on cardiomyocyte proliferation (discussed in the "Oxygen levels" section), has been suggested to be dependent on an increase in the number of resident macrophages (56). In contrast to the neonatal stage, adult mammalian hearts mainly undergo repair processes based on scarring and fibrosis, mostly as a result of the interaction between infiltrating immune cells (including macrophages) and fibroblasts [reviewed by Chen and colleagues (74)]. The paradoxical role of macrophages, triggering cardiac regeneration in lower vertebrates and neonatal mammals, and maladaptive remodeling in injured adult mammals, has been a matter of investigation.…”
Section: Cardiac Cell Populationsmentioning
confidence: 99%
“…In addition, macrophage depletion triggers AV block, which demonstrates their indispensability to the process of electrical conduction in the AV node in a steadystate[56]. Moreover, macrophages may cause conduction abnormalities [56], such as atrial fibrillation, ischemiainduced ventricular arrhythmias or arrhythmias associated with various inflammatory reactions (e.g., Lyme disease, Chagas, viral myocarditis)[58][59][60][61].…”
mentioning
confidence: 99%
“…Experimental evidence shows that cytokines directly affect cardiomyocytes altering the excitation–contraction coupling by affecting calcium handling, enabling spontaneous calcium release ( Fernández-Sada et al, 2017 ), and facilitating the substrate to ventricular arrhythmias ( Colman, 2019 ), ( Chen et al, 2020 ), ( Kouvas et al, 2018 ). For example, it has been shown that IL-1β increases calcium sparks in cardiomyocytes favoring arrhythmias associated with CaMKII oxidation and phosphorylation ( Monnerat et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed that the PD1-PD-L1 pathway protects the heart and lungs from autoimmune damage ( Colman, 2019 ) since PD-1 deficiency has been shown to induce fatal myocarditis in Murphy Roths Large (MRL) mice ( Chen et al, 2020 ). In this scenario, the direct binding of anti-PD-L1 to the PD-L1 expressed on cardiomyocytes contributes to the failure in maintaining chronic T-cell activation and thus the loss of tolerance.…”
Section: Discussionmentioning
confidence: 99%